Design, synthesis, biological evaluation and molecular docking studies of new chalcone derivatives containing diaryl ether moiety as potential anticancer agents and tubulin polymerization inhibitors - Wang, Guangcheng; Liu, Wenjing; Gong, Zipeng; Huang, Yong; Li, Yongjun; Peng, Zhiyun (Bioorganic chemistry, 2020)
[Display omitted] •Chalcone derivatives containing diaryl ether moiety were designed and synthesized.•In vitro anticancer activities were determined.•Compound 5b was found to be the most active compound.•Compound 5b inhibited tubulin polymerization.•Molecular docking studies were performed. A novel series of chalcone derivatives containing diaryl ether moiety (5a-5p) were designed, synthesized and evaluated their anti-tubulin polymerization activities and anticancer activities. Among them, compound 5b with 4-methoxy substitution on right aromatic ring was found to be most active on MCF-7, HepG2 and HCT116 cancer cell lines, with IC50 values of 3.44 ± 0.19, 4.64 ± 0.23, and 6.31 ± 0.27 μM, respectively. In vitro tubulin polymerization assay showed that 5b could effectively inhibit tubulin polymerization. Further mechanism studies revealed that 5b could induce G2/M phase arrest and cell apoptosis. Molecular docking studies revealed that 5b interact and bind at the colchicine binding site of the tubulin.